Valoración de la producción literaria de Jorge Zalamea desde la perspectiva crítica de Barbara H. Smith (2012)
ABSTRACT: This paper shows how some theoretical principles outlined by the American literary critic Barbara Herrnstein Smith, could be applied on the appraisal —including— of a specific work: that produced by the Colombian writer Jorge Zalamea (1905-1969). Smith’s formulation states that literary appraisal is usually due more to literary contextual criteria —which modify this appraisal— tan intrinsic factors of the work itself.